1992
DOI: 10.1080/07315724.1992.10718273
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose ingestion following exercise: selected cardiovascular, hormonal, renal, and metabolic effects.

Abstract: Carbohydrates, frequently consumed following exercise for glycogen resynthesis, have been shown to have other systemic effects in resting men. We examined the effects of postexercise sucrose (a disaccharide carbohydrate) ingestion on the renal, cardiovascular, and sympathetic nervous systems. Eight men consumed 1 l of water (W) or 1 l of a 200 g sucrose solution (S) following 1 hour of bicycle exercise at 70% heart rate reserve. Measurements were made during 2 hours of recovery. Heart rate and systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…Carbohydrate ingestion may have attenuated decreases seen in postexercise SBP by virtue of increased splanchnic perfusion and subsequent increases in HR and CO. Elevation in blood pressure and HR following carbo hydrate have been associated with increased sympathetic nervous system activity at rest [20,21]. However, in a previous study on normotensive men, we found no differ ence in plasma catecholamine levels when sucrose was consumed as compared to water ingestion postexercise [13]. Consequently, we did not measure catecholamines in the studies reported here.…”
Section: Cardiovascular Responsecontrasting
confidence: 68%
See 4 more Smart Citations
“…Carbohydrate ingestion may have attenuated decreases seen in postexercise SBP by virtue of increased splanchnic perfusion and subsequent increases in HR and CO. Elevation in blood pressure and HR following carbo hydrate have been associated with increased sympathetic nervous system activity at rest [20,21]. However, in a previous study on normotensive men, we found no differ ence in plasma catecholamine levels when sucrose was consumed as compared to water ingestion postexercise [13]. Consequently, we did not measure catecholamines in the studies reported here.…”
Section: Cardiovascular Responsecontrasting
confidence: 68%
“…Ingestion of a beverage containing 200 g of glucose polymer/fructose dissolved in 1 L of water, or approxi mately 2.7 g/kg body weight CHO, resulted in systemic changes similar to those reported following ingestion of a beverage containing 200 g of sucrose [13]. In general, the effects were less pronounced when the beverage contained 1.5 g/kg body weight of the commercial carbohydrate powder.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations